Choice of optimal technological operation mode of off-shore gas-condensate wells exploited in complicated conditions - Samadov, Tofig; Novruzova, Sudaba (Technology audit and production reserves, 2019)
The object of research is a new method for the approach to control the optimal technological regime of gas and gas condensate wells. It is noted that in order to optimize the technological regime of the well, by extracting liquid and solid particles, it is necessary to know the minimum value of gas production or gas flow rate, which, in turn, is provided by determining the corresponding value of the bottomhole pressure. To determine the bottomhole pressure at which the well reaches the optimal operating mode, an equation is obtained that has a complex structure with respect to the bottomhole pressure (pressure in the elevator shoe), for the solution of which the graphoanalytical method was used. The proposed method for optimizing the operation of gas and gas condensate wells was tested on the basis of actual data. And it is shown that it is possible to determine the optimal operating mode of gas and gas condensate wells by determining bottomhole pressure values at which liquid and solid particles are transported from the bottom of the wells to the earth's surface. In this case, the initial data for wells (No. 652 and 704) operated on the VII horizon of the Sangachal-Sea-Duvanny-Sea-Khara-Zira (Azerbaijan) field is used to determine their technological regimes. It is shown that it seems possible to increase the productivity of offshore gas and gas condensate wells by changing the design of their lifts and the proposed method allows to extract liquid and solid particles from the trunk to the earth's surface. For each case, the particle deposition rates in the gas medium and the gas flow rate in the elevator shoe were calculated. Judging by the value of the difference in the determined particle deposition rates and gas flow in the elevator shoe, the possibility of the formation of liquid plugs in the well is established. If a situation arises when the gas flow rate does not ensure the extraction of liquid particles on the earth's surface, it is proposed to change the diameters of the lifting pipes.